Effects of Comprehensive Land Consolidation on Farmers’ Livelihood Under Different Terrain Gradients - Rongshan Wan; Hui Yu; Dan Zhang; Bo Yang; Yanhong Huang (Land)
Comprehensive land consolidation (CLC) significantly impacts farmers’ sustainable development, particularly in southwestern mountainous areas with limited alternative livelihood options. However, existing studies have rarely considered the impact of CLC on farmers’ livelihoods under different terrain gradients in mountainous areas. Therefore, this study employs elevation, slope, and the terrain position index to divide terrain gradient zones. Based on 307 responses from household survey data, this study measures the changes in farmers’ livelihood capital and livelihood strategies before and after CLC and analyzes the heterogeneity of the impact of CLC under different terrain gradients. The results show the following: (1) The growth of farmers’ livelihood capital and the net effect of CLC showed the terrain gradient effect of medium-terrain areas > low-terrain areas > high-terrain areas. (2) Traditional agricultural types are transitioning to modern agricultural types and agriculture multi-employment types, while agriculture multi-employment types are shifting to non-agriculture multi-employment types. (3) The direct impact of CLC on livelihood transformation is significant in the low-terrain areas, whereas in the medium-terrain and high-terrain areas, the effects are primarily indirect through livelihood factors. This study can provide suggestions for the sustainable development of farmers in different topographic gradients in the Anning River basin.